Pengaruh Komposisi Media Tanam dan Konsentrasi Pupuk Organik Cair Berbahan Daun Gamal (Gliricidia sepium) Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) - Bagus Priyambodo; Kacung K Hariyono (Agrosains : Jurnal Penelitian Agronomi, 2024)
Mustard productivity in Indonesia tends to increase in 2019 by 10.72 tons/ha. However, this number is still below the yield potential of one of the national mustard varieties, namely the Puteri variety (PT Bintang Citra Asia), which has a yield potential of 20-25 tons/ha. An effort is needed to increase the productivity of national mustard by using liquid organic fertilizer (LOF) gamal leaves and managing the composition of the planting media. This study aims to determine the effect of the ratio between the doses of liquid organic fertilizer gamal leaves and the composition of the planting medium (soil, cow dung and husk charcoal) on polybag mustard plants. This study used CRD (completely randomized design) with 2 factors. The first factor is the planting medium (M) with 4 levels, namely soil (M0), soil + cow dung + husk charcoal = 1:1:1 (M1), 1:1:2 (M2), and 1:2:1 (M3) ). The second factor was gamal leaf POC (K) with 4 levels, namely without fertilizer application (K0), 80 ml/L (K1), 160 ml/L (K2) and 240 ml/L (K3). The data was then tested using ANOVA and 95% DMRT follow-up test. Treatment M3 and K3 were the best treatments for variable plant height, number of leaves, leaf width, leaf area index, fresh weight and dry weight. The interaction of the two M3K3 factors resulted in the highest average values for the 4 observational variables, namely plant height of 32.7 cm, leaf area index of 0.171 cm2, wet weight of 105.2 grams and dry weight of 8.57 grams. Soil, cow dung and rice husk charcoal and liquid organic fertilizer for gamal leaves can affect the growth and yield of mustard greens.